Attachment Style and Risk of Suicide Attempt Among New Soldiers in the U.S. Army. Issue 4 (2nd October 2022) - Wang, Jing; Naifeh, James A.; Herberman Mash, Holly B.; Morganstein, Joshua C.; Fullerton, Carol S.; Cozza, Stephen J.; Stein, Murray B.; Ursano, Robert J.
Abstract : Objective: Among U.S. Army soldiers suicide attempts (SAs) are a significant public health concern, particularly early in service. We examined the association of attachment style with SA and suicide ideation (SI) among U.S. Army soldiers. Methods: We analyzed survey data from new soldiers who participated in the Army Study to Assess Risk and Resilience in Servicemembers (Army STARRS). The sample consists of 38, 507 soldiers entering Basic Combat Training (BCT) between April 2011 and November 2012. Attachment style (secure, preoccupied, fearful, and dismissing) was assessed using items from the Relationship Questionnaire. Lifetime (pre-enlistment) SA and SI were assessed with a modified Columbia Suicide Severity Rating Scale. Logistic regression analyses examined associations of attachment style with lifetime SA, SI, and attempts among ideators, after adjusting for socio-demographic characteristics. Results: The secure attachment style was associated with lower odds of SA (OR = 0.76, 95% CI = 0.63–0.92), whereas preoccupied (OR = 4.63, 95% CI = 3.83–5.61), fearful (OR = 4.08, 95% CI = 3.38–4.94), or dismissing (OR = 1.56, 95% CI = 1.24–1.96) attachment styles were associated with higher odds of SA. Similar results were found for SI. Importantly, both preoccupied (OR = 1.67, 95% CI = 1.37–2.04) and fearful (OR = 1.70, 95% CI = 1.38–2.08) attachment were associated with attempts among ideators. Conclusion: These findings highlight the clinical importance of attachment style in predicting suicidal behavior and as possible targets for intervention. A critical next step is for prospective research to examine whether attachment style predicts future suicidal behavior.